2022
DOI: 10.1182/bloodadvances.2022008258
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of older adults with classic Hodgkin lymphoma in British Columbia

Abstract: Outcomes in older adults with classical Hodgkin lymphoma (cHL) have traditionally been poor, in part related to poor tolerance to standard chemotherapy. Herein, we evaluated the survival of patients aged >60 years with cHL in British Columbia in a population-based analysis. From 1961 to 2019, 744 pa-tients with newly diagnosed cHL were identified. With a median follow-up of 9 years, 5-year disease specific (DSS) and overall survival (OS) have improved by decade comparison (both p<0.001), remain-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In addition, observational studies suggest that anthracycline-free regimens are associated with worse lymphoma outcomes for both lymphoma types. 7 , 23 , 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, observational studies suggest that anthracycline-free regimens are associated with worse lymphoma outcomes for both lymphoma types. 7 , 23 , 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“… 33 Although novel agents may eventually eliminate the need for anthracyclines, at the present time, anthracycline-based regimens are associated with better lymphoma outcomes even in older patients with comorbidities, although further studies are needed to assess optimal regimens for patients with pre-existing HF, multiple comorbidities, or documented geriatric syndrome. 7 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the 5% TRM reported in a population-based study in British Columbia, Canada, also in the modern era, but the latter study provided no clear definition of TRM. 28 Prospective studies of combination chemotherapy in elderly HL patients have reported rates ranging from 7% to 18%. 14 , 15 , 27 , 30 Regimens that include novel drugs, such as brentuximab vedotin or programmed cell death protein-1 inhibitors are also studied in selected elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…38 Corresponding numbers in the British Columbia cohort treated since 2000, where 160 deaths had occurred in the 327 patients treated with curative intent, were 49.4% for deaths from HL (including deaths from immediate treatment toxicity), 19.4% for secondary malignancies (including other hematologic malignancies), and 8.8% for CVD, all possibly more representative comparators to our data. 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation